2020
DOI: 10.1039/d0ra01890b
|View full text |Cite
|
Sign up to set email alerts
|

Nickel–cobalt hydroxide: a positive electrode for supercapacitor applications

Abstract: So far, numerous metal oxides and metal hydroxides have been reported as an electrode material, a critical component in supercapacitors that determines the operation window of the capacitor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(32 citation statements)
references
References 44 publications
4
28
0
Order By: Relevance
“…In addition, the crystallization and morphology of nickel sulfide are primarily tuned by controlling the sulfur source in the reaction. In general, nickel sulfide is synthesized by dissolving metal salts, such as nickel acetate, nitrate, and chloride, and sulfur precursors, such as sodium sulfate, thioacetamide (TAA), thiourea (TU), and sodium thiosulfate, in solution [28][29][30][31][32][33][34]. Chen et al used Ni(NO 3 ) 2 •6H 2 O and TU to directly prepare Ni 3 S 2 on Ni foam (NF) [35], and Wu et al used TAA and NF to prepare rod-like Ni 3 S 2 [36].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the crystallization and morphology of nickel sulfide are primarily tuned by controlling the sulfur source in the reaction. In general, nickel sulfide is synthesized by dissolving metal salts, such as nickel acetate, nitrate, and chloride, and sulfur precursors, such as sodium sulfate, thioacetamide (TAA), thiourea (TU), and sodium thiosulfate, in solution [28][29][30][31][32][33][34]. Chen et al used Ni(NO 3 ) 2 •6H 2 O and TU to directly prepare Ni 3 S 2 on Ni foam (NF) [35], and Wu et al used TAA and NF to prepare rod-like Ni 3 S 2 [36].…”
Section: Introductionmentioning
confidence: 99%
“…They found that the mixed metal hydroxide had better capacitance than bare Ni(OH) 2 due to the presence of Co and exhibited excellent retention of 96.26% up to 2000 cycles. 132 A binary transition metal oxide based on zinc and iron was mixed with reduced graphene oxide, leading to an improved ZnFe 2 O 4 -rGO nanohybrid structure that was studied by Askari et al The ZnFe 2 O 4 -rGO electrodes yielded a capacitance of 1419 F g −1 with 93% cyclic stability after 5000 charge/discharge cycles, making them an opportune candidate for supercapacitor electrodes. 133 Cheng et al reported a core− shell-structured metal hydroxide on CNT synthesized by a chemical method for high-performance supercapacitor electrodes.…”
Section: ■ Choice Of Electrode Materialsmentioning
confidence: 99%
“…The first mechanism is based on the surface adsorption of electrolyte cations (Na ? ) on Fe(OH) 2 @Cd(OH) 2 [29,30]: The second one involves the intercalation of alkali metal cations Na ? .…”
Section: Electrochemical Supercapacitive Performancementioning
confidence: 99%